Néfesh e Basar : a relação corpo-alma na Bíblia Hebraica e suas implicações para a cultura somática hodierna - Prazeres, Alexandre de Jesus dos (2013)
This work is a study of the body-soul relationship in the Hebrew Bible and its implications for today's culture body, guided by the following general objective: to understand the biblical concept of man-Semitic, through the study of Hebrew terms semantic vp,n< /n#P#v/ and rf'B' /B*c*r/, and its implications for the somatic culture today. That in turn breaks down into three specific objectives. The first, noted how issues of body-soul relationship were answered throughout history by theologians and philosophers, and their influence in relation to the formation of Western culture. This objective will guide the first chapter that will present an overview of the body-soul relationship. The second, extracting, examining meaning of the terms vp,n< /n#P#v/ and rf'B' /B*c*r/ in passages where the same were employed, implications related to a perception of ideational and conceptual Semitic assumptions regarding human being. This objective will be pursued throughout the second chapter which is an anthropological approach to the Hebrew Bible. And the third, confront the notion of biblical-Semitic man with symptoms of somatic culture today. This objective will guide the third chapter presents the implications of the terms vp,n< /n#P#v/ and rf'B' /B*c*r/ for somatic culture today. In terms of structure and methodology, this work will follow a logical order, it will start exposing the debate on the body-soul relationship through the panorama presented in the first chapter, which is the philosophical axis; followed by analysis of exegetical texts Hebrew Bible, this is the axis anthropological; and eventually end up confronting the extracted contents of the Hebrew Bible exegetically with the symptoms of somatic culture today, this will be the axis theological and sociological.